Organocatalysis in Synthesis of Pyrrolidine Derivatives via Cycloaddition Reactions of Azomethine Ylides - Randjelovic, Jelena; Simic, Milena; Tasic, Gordana; Husinec, Suren; Savic, Vladimir (Current Organic Chemistry, 2014)
Cycloaddition reactions of azomethine ylides are the most direct way to synthesise pyrrolidine derivatives. They have been studied for several decades and have become an indispensable tool in synthesis of pyrrolidines and pyrrolidine derived natural products. Amongst many methods for generating azomethine ylides, various processes involving imines derived from amino acid esters have been the most frequently studied. The use of Lewis acids to promote imine-ylide-cycloaddition sequence under mild conditions, in recent years, has led to the development of highly stereoselective metal catalysed methodologies for the preparation of pyrrolidine derivatives. In the last few years, the concept of organocatalysis has been incorporated in cycloaddition reactions of azomethine ylides providing an alternative access to chiral pyrrolidines. Several classes of typical organocatalysts such as prolines, phosphoric acids, thioureas, guanidines and sulphuric acid derivatives have been used for these purposes. Various mechanistic pathways have been proposed, based on either the activation of only one reacting partner, 1,3-dipole (imine) or dipolarophile (alkene), or both of them simultaneously. While the first three classes of organocatalysts appear to afford pyrrolidines, generally, in good yields and with high levels of stereoselectivity, guanidines and sulphuric acid derivatives are less efficient, but also the least studied catalyst group. A whole range of electron deficient dipolarophiles (alkenes) have been used in these cycloaddition processes, while, regarding the dipole precursor imine, aromatic aldimines seem to be more efficient than their aliphatic equivalents. There is no doubt that the recent progress in organocatalytic cycloadditions of azomethine ylides created new possibilities for synthesis of pyrrolidine derivatives and enriched this useful synthetic methodology.
Keywords: stereoselectivity